Prokes rematri Web-based App: Development, Testing and Construct Validation of Content to Control Undernutrition at Female Teenager as Early Prevent Stunting in Life Cycle - Vilda Ana Veria Setyawati; Ari Yuniastuti; Handayani, Oktia Woro Kasmini; Farida, Eko (Science and Technology Research Centre Universitas PGRI Semarang, 2025)
Several measurements of female teenager undernutrition risk factors have been carried out, but the data are limited and not collected well. Technology approach needed to solve at this problem. This research was conducted to develop Prokes rematri web-based app and analysis CFA and EFA as construct validity. The variables and items as content of beta version were obtained from literature reviews and in-depth interviews who stake holder stunting program as subjects. In this study we limit the science scope about public health, nutrition, and statistic. Data analysis using explanatory factor analysis (EFA) and confirmatory factor analysis (CFA). In conclusion, we had developed Prokes Rematri We-Based app and have blackbox tested. In the other hand, 40 items question as end result of construct validated by EFA and CFA. The scope of questionnaire consist of four topics, that are youth nutrition practice, community support, youth nutrition knowledge, and internal factor of youth nutrition.